PENGENALAN KONSEP MATEMATIKA MELALUI PENGGUNAAN BAHAN ALAM PADA ANAK USIA 5-6 TAHUN - Rachmawati, Rachmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract:The purpose of this research is to know the cognitive ability of children in the introduction of mathematical concepts through the use of natural materials in children aged 5-6 years in PAUD Bersinar Kecamatan Pontianak Selatan. Problems that are often found by teachers only use the existing learning media and less creative use of natural materials that exist around PAUD PAUD institutions. Whereas the method used is descriptive method. The results obtained from the 1st cycle of assessment categories developed as expected (BSH) increased to 27%. In cycle 2 the introduction of mathematical concepts using natural ingredients with the category of developing children's assessment as expected increased to 47% and even increased to 70% of children, and 7% of the category categories developed very well in the introduction of mathematical concepts using natural materials.Keyword : Mathematical Concept, Use of Natural Materials